Tradisi Pawai Obor dalam Memperingati Tahun Baru Islam di Desa Bukit Peninjauan II Seluma - Edon Sholeh Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
The torch parade, held annually to commemorate the Islamic New Year (1 Muharram) in Desa Bukit Peninjauan II, serves as a vital cultural and communal event that underscores both social cohesion and cultural preservation. This study investigates the significance and impact of the torch parade on the local community, focusing on how it functions as a vehicle for cultural continuity and social unity. The objectives of the study are to analyze the ways in which the parade fosters community involvement, preserves local traditions, and strengthens social bonds. The methodology employed includes qualitative observations and interviews with key participants and organizers involved in the event. Data collection involved direct observations during the parade, interviews with community members, and analysis of participation records and event feedback. The findings reveal that the parade significantly contributes to the preservation of cultural heritage by engaging multiple generations in the celebration. It acts as a catalyst for social interaction, enhancing community solidarity and collective identity. Additionally, the event provides a platform for the younger generation to actively participate in cultural practices, thereby ensuring the transmission of cultural values. The study concludes that the torch parade not only serves as a festive occasion but also plays a crucial role in maintaining and reviving traditional practices within the community. By fostering a strong sense of communal identity and pride, the event supports the broader objectives of cultural preservation and social cohesion.